Amblyomma hadanii n. sp. (Acari: Ixodidae), a tick from northwestern Argentina previously confused with Amblyomma coelebs Neumann, 1899 - Nava, Santiago (2014)
All stages of Amblyomma hadanii n. sp. (Acari: Ixodidae) are described from northwestern Argentina. The diagnostic characters for males are a combination of the pattern of scutal ornamentation, basis capituli dorsally rectangular with cornua, coxa I with two subequal spurs (the internal wider, the external longer), coxae II-III with a single spur, coxa IV with a single spur not reaching level of anus, ventral plates irregular in shape (larger and sometimes with a small incision on festoons 4, 5 and 6) and hypostome spatulate with dental formula 3/3 in 7–8 rows. The diagnostic characters for the females are a combination of scutal ornamentation, postero-lateral margins of scutum slightly convex, coxa I with two subequal spurs (the internal wider, the external longer), basis capituli dorsally rectangular, porose areas rounded, genital aperture U-shaped, and hypostome spatulate with dental formula 3/3 in 7–8 rows. Diagnosis of nymphs can be performed by a combination of basis capituli rectangular, scutum with large punctations in the lateral fields and small punctations in the central field, and cervical groove short and ending as a small shallow depression at the eye level. Larvae are diagnosed by the shape of basis capituli, scutum with with posterior margin slightly convex, and legs with coxa I with 2 triangular spur (the external longer than the internal), and with coxae II and III each with 1 triangular spur. The hosts recorded for this new tick species are Tapirus terrestris (Linnaeus), horse, cattle, dog and humans. Analyses of a 410 bp fragment of the mitochondrial 16S rRNA gene and the complete sequence of the nuclear 18S rRNA gene supported the description of A. hadanii as a new species.